Conservative surgical approach and aesthetic management of a focal gingival hyperplastic lesion - Anand Mohan; Lokesh Kumar; Priyanka K. Cholan; Niroshini Rajaram (Clinics and Practice, 2014)
Focal reactive hyperplastic lesions of the gingiva are quite common soft tissue enlargements of the oral cavity. Presence of local factors, tissue irritation and endocrinal discrepancies contribute to its etiology. The fact that these lesions are caused by diverse pathological conditions and its histo-pathological resemblances poses a great diagnostic challenge. Due to the site predilection of the these lesions to the maxillary anterior region, this article presents a case report of focal gingival hyperplastic lesion in the anterior maxillary region and its conservative management leading to pleasing results and soft tissue esthetics.